252 Extra ovarian endodermal sinus tumour diagnosed at caesarean section. (13th November 2020) - West, S; Gard, G; Burton, G
Abstract : The case is of 38 y.o a G2P1 woman who had a previous normal term pregnancy and Caesarean Section for Breech Presentstion. She had no significant medical history prior to pregnancy. Antenatal screening was unremarkable, and a 19-week morphology scan was normal. She presented at 31 weeks with Left Iliac Fossa pain and bleeding. Ultrasound reported a 116 × 109 × 105 cm possible Cervical Fibroid and a complex left cystic collection and a fetal transverse lie. She had premature ruputure of membranes 2 days later and underwent emergency Caesarean section at 32 weeks gestation for unstable lie in the setting of ongoing pain and bleeding. At time of Caesarean section, a healthy 2090 g male was delivered and uterine incision closed without incident. Examination of the Pouch of Douglas revealed loculted fluid in the left fossae and large mass posterior to the vagina and separate to normal uterus, ovaries and Fallopian tubes. A Gynaecology Oncologist attended and performed excision of the large mass and peritoneal disease and a colorectal surgeon assisted with resection of bowel pathology. Frozen section revealed a poorly differentiated malignant tumour. Macroscopic appearance of the uterus, fallopian tubes and ovaries was unremarkable at time of excision and a decision was made to leave these tissues in situ. Final pathology revealed an endodermal sinus tumour. Serum AFP was 1515kiu/L and HCG was 3.0 IU/L. Literature review indicates extra ovarian Yolk sac tumours are rare, with diagnosis at Caesarean section extremely uncommon.